KOMUNIKASI REMAJA PENGGUNA GAME ONLINE PUBG MOBILE (Studi Kasus Remaja Usia 17-20 di Jorong Rajo Dani Kecamatan Padang Ganting) - Fitri, Elviza; Mastanora, Refika (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The main issue discussed in this research is how the verbal and non-verbal communication of adolescents is affected by their dependency on PlayerUnknown's Battlegrounds Mobile game. The background of this research is based on the excessive involvement of adolescents in online gaming, leading to dependency and changes in communication styles among individuals, both verbally and non-verbally. The purpose of this thesis is to describe the forms of verbal and non-verbal communication among users of the online game PlayerUnknown's Battlegrounds Mobile and to describe the forms of dependency caused by adolescents playing PUBG Mobile in Jorong Rajo Dani, Padang Ganting District. The research design used in this study is field research with a qualitative descriptive approach. The descriptive method aims to portray a phenomenon that occurs in a natural setting. Data collection techniques used in this research are interviews and documentation. The analysis techniques employed include data reduction, data presentation, and drawing conclusions or verification. The results of the research can be summarized as follows: First, the communication process occurs effectively, both in face-to-face interactions and online through features such as chatting and voice communication, accompanied by stickers and emojis as means of self-expression during online communication. Second, based on the research conducted, it was found that the forms of dependency caused by adolescents playing PlayerUnknown's Battlegrounds Mobile include salience, tolerance, mood modification, withdrawal, relapse, conflict, and problems. Therefore, it can be concluded that the informants tend to experience salience and tolerance dependency.